2020
DOI: 10.16916/aded.681425
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Writing Skills of the First Grade Elementary School Students

Abstract: Bu araştırmada ilköğretim birinci sınıf öğrencilerinin dik temel yazı okunaklılığını ve hızını incelemek amacıyla betimsel tarama yöntemi kullanılmıştır. Çalışma 2019-2020 eğitim öğretim yılının birinci döneminde Burdur'da bir devlet okulunda eğitim gören 13'ü kız, 12'si erkek olmak üzere 25 birinci sınıf öğrencisine uygulanmıştır. Veri toplama aracı olarak "Dikte Çalışması Takip Formu" ve "İlkokullar İçin Hikâye Yazmaya Yönelik Bütüncül Puanlama Yönergesi" birinci sınıflara uyarlanarak kullanılmıştır. Öğrenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…The relevant literature review has revealed that there are a number of studies conducted on the legibility of students' handwriting at the first grade (Aktaş & Bakkaloğlu, 2021;Gök & Baş, 2020;Okatan & Özer, 2020;Ulu, 2019) as well as those conducted with students at other grade levels (Fogel, Rosenblum & Barnett, 2022;Ghorbani et al, 2020;Schwellnus et al, 2012;Yıldız & Ateş, 2010). Besides being a factor affecting the writing skill, legibility in and of itself is also affected by some factors.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature review has revealed that there are a number of studies conducted on the legibility of students' handwriting at the first grade (Aktaş & Bakkaloğlu, 2021;Gök & Baş, 2020;Okatan & Özer, 2020;Ulu, 2019) as well as those conducted with students at other grade levels (Fogel, Rosenblum & Barnett, 2022;Ghorbani et al, 2020;Schwellnus et al, 2012;Yıldız & Ateş, 2010). Besides being a factor affecting the writing skill, legibility in and of itself is also affected by some factors.…”
Section: Introductionmentioning
confidence: 99%